Inquiry into vertical movements of the earth‘s crust based on samples from eastern Lithuania - Puziene, Ruta; Anikeniene, Asta; Karsokiene, Gitana (Geodesy and Cartography, 2014)
In the research of vertical movements of the earth’s crust, examination of statistical correlations between the measured vertical movements of the earth’s crust and territorial geo-indexes is accomplished with the help of mathematical statistical analysis. Availability of the precise repeated levelling measuring data coupled with the preferred research methodology offer a chance to determine and predict recent vertical movements of the earth’s crust. For the inquiry into recent vertical movements of the earth’s crust, a Lithuanian class I vertical network levelling polygon was used. Drawing on measurements made in the polygon, vertical velocities of earth’s crust movements were calculated along the following levelling lines. For determining the relations shared by vertical movements of the earth’s crust and territorial geo-parameters, the following territory-defining parameters are accepted. Examination of the special qualities of relations shared by vertical movements of the earth’s crust and geo-parameters in the territory under research contributed to the computation of correlation matrices. Regression models are worked out taking into consideration only particular territory-defining geo-parameters, i.e. only those parameters which exhibit the following correlation coefficient value of the vertical earth’s crust movement velocity: r ≥ 0.50. A forecast of the velocities pertaining to vertical movements of the earth’s crust in the territory under examination was made with the application of regression models. Further in the process of this research, a map was compiled specifying the velocities of vertical movements of the earth’s crust in the territory. In the eastern part of this territory, the earth’s crust rises at a rate of up to 3 mm/year; while in the western part of it, the earth crust lowers at a rate of up to –1.5 mm/year. In order to pinpoint territories characterised by temperate and regular rising/lowering or intensive rising/lowering, a map of horizontal gradients of recent vertical earth crust movements in the territory enclosed by levelling polygon was compiled.